Aktivitas Fisik Komunitas sebagai Determinan Tidur dan Kognisi Lansia - Widanita, Neva; Qurrotuaini, Risma; Suhartoyo, Topo; Bangun, Septiono; Febriani, Ayu Rizky (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Population aging is associated with an increased prevalence of sleep disturbances and cognitive decline, which may reduce independence and quality of life among older adults. This study aimed to examine the relationship between physical activity, sleep quality, and cognitive function among older adults participating in a community-based exercise program (Sang Surya gymnastics). A quantitative correlational design was applied involving 33 older adults. Physical activity was assessed using the Physical Activity Scale for the Elderly (PASE), sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and cognitive function using the Mini-Mental State Examination (MMSE). The results showed that participants had moderate physical activity levels (PASE = 112.36 ± 28.47), suboptimal sleep quality (PSQI = 6.21 ± 2.14), and cognitive function ranging from normal to mild impairment (MMSE = 24.87 ± 3.12). Physical activity was significantly associated with cognitive function (r = −0.39, p < 0.05), whereas its association with sleep quality was weak and not statistically significant (r = −0.11, p > 0.05), and sleep quality showed a weak, non-significant correlation with cognitive function (r = 0.21, p > 0.05). These findings indicate that community-based physical activity is more closely related to cognitive function than sleep quality among older adults, suggesting that physical activity programs may contribute to cognitive health maintenance, while improvements in sleep quality may require additional targeted interventions. Keywords: physical activity; sleep quality; cognitive function; older adults; community-based exercise